Ecological connectivity between land and sea: a review. Issue 1 (22nd December 2017) - Fang, Xiaodong; Hou, Xiyong; Li, Xiaowei; Hou, Wan; Nakaoka, Masahiro; Yu, Xiubo
Abstract: Land–sea ecological connectivity refers to the interaction (convenience or hindrance) of certain physical, chemical and biological processes between terrestrial and marine ecosystems. Research on land–sea ecological connectivity can provide important scientific bases for the conservation and restoration of biodiversity and ecosystems in terrestrial and coastal areas. On the basis of a literature summary of ecological connectivity, this paper focuses on the following: (1) summarizing basic concepts, representative phenomena on multiple spatiotemporal scales, and analysis methods of land–sea ecological connectivity; (2) discussion of the applications of land–sea ecological connectivity; (3) discussion of the relationship between human activities and land–sea ecological connectivity; (4) presentation of perspectives and recommendations on ecological restoration, protection, and biodiversity research, with emphasis on the principle of land–sea ecological connectivity. On the whole, we believe such connectivity in a region varies with changes in multiple physical and artificial factors, such as climate, land cover, biotic community and human activities. Human activities such as land use, engineering construction, urbanization and industrialization have continuously increased and cause irreversible disturbance and destruction of land–sea ecological connectivity, thereby threatening biodiversity and ecosystem services at various spatiotemporal scales. Hence, achievements of theoretical research and practical experience in ecological connectivity should be fully applied in coastal areas to maintain and restore land–sea ecological connectivity and remedy various problems that arise from the blockage and damage of ecosystem services.